DOSE OPTIMIZATION OF FOLIAR APPLIED GIBBERELLIC ACID FOR NEWLY DEVELOPED OF HYBRID RICE LINES IN EGYPT - Omar, Abd Elhamid Mohamed; Khalifa, Mohammed Abdelmonem; Elhity, Mahmoud Abdelhamid; Yousef, Mahmoud Ibrahim Abo; Kızılgeçi, Ferhat; Öztürk, Ferhat (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
Gibberellic acid (GA(3)) plays a vital role in boosting hybrid rice yield, however, fresh research needs to be done for its dose optimization especially for newly developed hybrid rice lines. To fill this research gap, an investigation was conducted at the experimental farm of Sakha Agricultural Research Station, Kafrelsheikh, Egypt during two growing seasons of 2017 and 2018. The main objective of this study was to evaluate the impact of GA(3) application on hybrid rice lines for boosting seed production. Egyptian hybrid No.1 and G46 A/Giza 178 R were the hybrid rice lines, while GA(3) in four doses viz. 0, 250, 300 and 350 g/ha were applied. The experimental design was split plot with three replications, where the main plot was devoted to hybrid rice lines, while the subplots had different doses of GA(3). The results showed that the best desirable values for the studied characteristics especially for hybrid seed yield (2.5 t/ha) were recorded of the hybrid combination IR69625/Giza 178 followed by G46A/Giza178 with the highest dose of GA(3). It is concluded that foliage application of GA(3)@ 350 g/ha has the potential to enhance hybrid rice seed production. while hybrid rice line Giza 178 can be recommended for general adoption in the irrigated regions of Egypt.
Keywords: Gibberellic acid; Morphology; yield; Hybrid rice